The Regulation of Target Genes by Co-occupancy of Transcription Factors, c-Myc and Mxi1 with Max in the Mouse Cell Line - Wang, Hui; Liu, Yuan; Guan, Hua; Fan, Guo-Liang (Current Bioinformatics, 2020)
Background: The regulatory function of transcription factors on genes is not only related to the location of binding genes and its related functions, but is also related to the methods of binding. Objective: It is necessary to study the regulation effects in different binding methods on target genes. Methods: In this study, we provided a reliable theoretical basis for studying gene expression regulation of co-binding transcription factors and further revealed the specific regulation of transcription factor co-binding in cancer cells. Results: Transcription factors tend to combine with other transcription factors in the regulatory region to form a competitive or synergistic relationship to regulate target genes accurately. Conclusion: We found that up-regulated genes in cancer cells were involved in the regulation of their own immune system related to the normal cells.
Keywords: target genes